Students Expressive Speech Acts Operated In Teaching Learning Conversation In Elti Gramedia Surakarta - NUGRAHA, Risma Ardiansyah; , Agus Wijayanto, Ph.D; , Dr. Dwi Haryanti, M.Hum (2015)
The objectives of this research were to describe the realizations of expressive speech acts used by students, to explain the students' strategies in their expressive utterances, to explain the students' intentions in their expressive utterances. The data of this research were collected from the teaching-learning conversation in ELTI GRAMEDIA Surakarta employed by students aged 19-23 years old. There were several steps done to analyze these data, i.e. describing the data in the form of dialogue and elaborating the context of conversation and expressive acts. Other steps to identify the strategies of students' expressive act are: describing the data in the form of dialogue, describing the context and analyzing strategies used there. Based on the analysis, it was found out that students were often unaware of their expressive act and they employed only common expressive speech acts in their talk. The types of expressive acts identified are thanking, congratulating, blaming, praising and apologizing. In terms of their strategy, the students barely made a direct expressive speech act in their utterance. This seems to imply their low level of English proficiency.